Remarkable Response of EGFR- and HER2-Amplified Metastatic Colon Cancer to Pyrotinib After Failed Multiline Treatments: A Case Report and Literature Review - Li, Hong-Shuai; Yang, Li-Li; Zhang, Ming-Yi; Cheng, Ke; Chen, Ye; Liu, Ji-Yan (Frontiers in Oncology, 2020)
Human epidermal growth factor receptor 2 (HER2) has been verified as a valuable biomarker and treatment target in metastatic colorectal cancer (mCRC). Pyrotinib, a novel irreversible HER2/epidermal growth factor receptor (EGFR) dual tyrosine kinase inhibitor, can efficiently inhibit the proliferation of HER2-positive cancer cells in many tumors. We report a case of a 40-year-old woman with both HER2- and EGFR-amplified metastatic colon cancer, who developed refractory disease resistant to multiline therapies (including trastuzumab with lapatinib) but achieved a remarkable response after pyrotinib treatment. For patients with HER2-positive mCRC, who have developed resistance to trastuzumab and lapatinib, pyrotinib is a promising new candidate, which can be used as salvage therapy.